Investigation of a suspected measles outbreak in a security crisis and border zone, Cinkansé, Burkina Faso, November 2022 - Morou Nikiema; Aloukoumane Lengane; Denis Yelbeogo; Bérenger Kabore; Madi Saidou Bagaya; Issa Guire; Abdramane Sawadogo; Souleymane Kabore; Yamregma Kabore (Journal of Interventional Epidemiology and Public Health)
Introduction: From September 12, 2022, to October 23, 2022, the border CSPS (Health and Social Promotion Center) in Cinkansé reported a total of 22 suspected cases of measles. In response to this unusual number of suspected cases, we investigated to confirm the outbreak and guide the response. Methods: We conducted a cross-sectional study. The investigation took place over two days, from October 31 to November 1, 2022. A suspected case of measles was defined as any person residing in Cinkansé and presenting between August 29 and November 1, 2022, with fever, maculopapular rash, cough, cold or conjunctivitis. A confirmed case was any suspected case with positive measles virus IgM. We abstracted data from the consultation registers and complimented this with primary data collected through clinical observation and individual interviews. A vaccination coverage survey was carried out in the community. The collection tools used included an interview guide and a documentary analysis framework. Data analysis was carried out with Epi info and we calculated proportions. Results: We found 44 suspected cases of measles, including 2 during an active community search. Of these, 77.3% (34/44) lived in Cinkansé_Burkina and 22.7% (10/44) in Cinkassé_Togo. The average age of cases is 2.2 years. Extreme ages are represented by cases aged 3 months and 34 years. Not all cases received their second dose of measles-rubella vaccine (RR2). Blood samples were taken from 33/44 cases, but only 11 samples were analyzed by the laboratory due to a lack of reagent availability. Of the 11 samples analyzed, 9 were positive for measles IgM. For the other cases, we had 10 epidemiologically confirmed cases and 23 clinically compatible cases. The measles epidemic was confirmed on November 16, 2022. The vaccine coverage survey showed that 61.90% (13/21) of children had received their second dose of measles-rubella vaccine (RR2). We conducted a joint reactive vaccination campaign with Togo from December 5 to 11, 2022. The target was subjects aged 6 months to 14 years. A total of 47,592 children in this age group benefited from this vaccination, i.e. coverage of 115.20%. Vaccination led to a gradual decline in the number of cases, followed by the declaration of the end of the epidemic on March 5, 2023 Conclusion: A measles epidemic was confirmed. Reinforced epidemiological surveillance at all levels and cross-border collaboration could prevent futures epidemics.